The Role of Social Acceptance as A Mediator Variable in The Influence of Environmental Awareness on Willingness to Pay for Waste to Energy - Soeharso, Silverius Y; Wicaksana, Seta A (RSF Conference Series: Business, Management and Social Sciences, 2024)
This research aims to determine the role of Social Acceptance as a mediator variable on the influence of Environmental Awareness on Willingness to Pay for Waste to Energy. Participants in this research were the general public aged over 16 years. A total of 200 respondents were obtained through convenience sampling techniques. The measuring instruments used in this research are the social acceptance scale (SAS), environmental awareness scale (EAS), and willingness to pay scale (WTPS). The analysis technique used in this research uses the Structural Equation Modeling (SEM) and path analysis tests. The results of this study show that social acceptance of waste to energy cannot play a significant role as a mediator in the relationship between environmental awareness and willingness to pay for waste to energy. Other findings in this research are that environmental awareness has a significant direct effect on social acceptance of waste to energy, environmental awareness directly affects willingness to pay for waste to energy, and social acceptance of waste to energy does not affect willingness to pay for waste to energy. Suggestions for further research could deepen further into what factors can influence the willingness to pay for waste to energy.